(untitled) (Microbes and Health, 2013)
Of all serological tests enzyme-linked immunosorbent assay (ELISA) is still considered the gold standard for the detection of antigens and antibodies of either macro or micro-organisms worldwide. The ELISA kits for serum antibody detection against many viruses and other micro-organisms of both man and animals are available in the market. Whereas, antigen detection ELISA kits for Newcastle disease virus (NDV) is not yet available in Bangladesh. The Present study was designed for the development of an economically feasible In-house Sandwich ELISA and to test its sensitivity and specificity for the detection of NDV antigens from clinically suspected field samples. 96- well flat bottom polystyrene plates coated with hyperimmune polyclonal serum against NDV raised in rabbits was used to capture NDV antigens. The anti-rabbit IgG and DAB with 30% H2O2 were used as conjugate and substrate respectively for standardization of the test method. The plate coated with serum diluted 10-3 was found suitable for capturing maximum antigen of NDV by the In-house Sandwich ELISA. The cut-off value of the present ELISA test was calculated as 0.855 and was able to capture the viral antigen present in the 10-4 fold dilution of allantoic fluid (AF) which is equivalent to 1HA unit, indicating the highest degree of sensitivity of the newly developed ELISA. In case of field samples, the newly developed ELISA kit was able to detect 100% viral antigens of NDV present in the feces, 95.50% of the brain tissue and oro-nasal swab and 94.12% of colon swab samples of either naturally and experimentally infected birds in this study. The ND virus specific polyclonal antibody used in the kit bind only with ND virus without any cross reactive antigens of other viruses of chicken like Avian influenza virus (AIV) and Infectious bursal disease viruses (IBDV). Therefore, findings of the present study clearly indicates that the newly developed In-house Sandwich ELISA kit can be used for rapid confirmatory diagnosis of Newcastle disease (ND) with minimum cost, using any kind of field samples from either sick or dead birds. DOI: http://dx.doi.org/10.3329/mh.v1i2.14093 Microbes and Health, 2012 1(2): 65-71